Pelatihan Optimalisasi Nilai Ekonomi Lahan Untuk Penetapan Komoditas Unggulan di Kecamatan Gerung Kabupaten Lombok Barat - Bambang Dipokusumo; Anwar; Sri Supartiningsih; Muhammad Nursan (Universitas Mataram, 2022)
The objectives of implementing this community service are: (1) increasing farmers' knowledge and skills about land optimization techniques or land economic assessment (2) increasing farmers' knowledge in aspects of superior commodity selection methods and (3) increasing farmers' knowledge and skills in farming bookkeeping. The implementation uses the adult education method (andragogy), which is to systematically reconstruct the knowledge and experience of participants in order to provide practical benefits, namely increasing their knowledge and skills. Implementation consists of training and mentoring. The training materials are land economic assessment and techniques for determining/ selecting superior commodities. The results of community service provide an illustration that there is an increase in farmers' knowledge and skills in classifying the economic value of land, superior commodities and farming bookkeeping